B Cell IgD Deletion Prevents Alveolar Bone Loss Following Murine Oral Infection - Baker, Pamela J.; Boutaugh, Nicole Ryan; Tiffany, Michaela; Roopenian, Derry C. (Interdisciplinary Perspectives on Infectious Diseases, 2009)
Periodontal disease is one of the most common infectious diseases of humans. Immuneresponses to infection trigger loss of alveolar bone from the jaw and eventual tooth loss. We investigated the contribution of B cell IgD to alveolar bone loss by comparing the response of B cell normal BALB/cJ mice and IgD deficient BALB/c-Igh-5−/−J mice to oral infection with Porphyromonas gingivalis, a gram-negative periodontopathic bacteriumfrom humans. P. gingivalis-infected normal mice lost bone. Specific antibody to P. gingivalis was lower and oral colonization was higher in IgD deficient mice; yet bone loss was completely absent. Infection increased the proportion of CD69+ activated B cellsand CD4+ T cells in immune normal mice compared to IgD deficient mice. These data suggest that IgD is an important mediator of alveolar bone resorption, possibly through antigen-specific coactivation of B cells and CD4+ T cells.